An unusual case of herpes simplex virus pneumonia with cavitary and necrotic changes - Lee, Hong Lyeol (Respir Med Case Rep, 2020)
Ground glass opacities, consolidation, and pleural effusions are observed in herpes simplex virus (HSV) pneumonia. Neither necrosis nor cavitation has been reported in areas of parenchymal disease. We describe a case of HSV pneumonia with unusual multiple cavitary and necrotic changes in an immunocompetent person. To our knowledge, this is the first reported case of HSV pneumonia with multiple cavitary and necrotic changes in areas of consolidation and nodules.